2001
DOI: 10.1038/nsb738
|View full text |Cite
|
Sign up to set email alerts
|

Domain alternation switches B12-dependent methionine synthase to the activation conformation

Abstract: B(12)-dependent methionine synthase (MetH) from Escherichia coli is a large modular protein that uses bound cobalamin as an intermediate methyl carrier. Major domain rearrangements have been postulated to explain how cobalamin reacts with three different substrates: homocysteine, methyltetrahydrofolate and S-adenosylmethionine (AdoMet). Here we describe the 3.0 A structure of a 65 kDa C-terminal fragment of MetH that spans the cobalamin- and AdoMet-binding domains, arranged in a conformation suitable for the m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

8
99
0
1

Year Published

2003
2003
2010
2010

Publication Types

Select...
4
4

Relationship

2
6

Authors

Journals

citations
Cited by 100 publications
(108 citation statements)
references
References 24 publications
8
99
0
1
Order By: Relevance
“…Whereas the fold of the individual domains is well conserved, the orientation between the two domains drastically differs, indicated by a relative rotation and translation of 51.4°and 28.0 Å, respectively, between the helical domains of MtaC and MetH. An orientation similar to that in MtaC was found in the structure of the complex between the cobalaminand AdoMet-binding domains of MetH (39).…”
Section: Structure Of Mtab and The Binding Mode Of The Catalytic Zincmentioning
confidence: 82%
See 1 more Smart Citation
“…Whereas the fold of the individual domains is well conserved, the orientation between the two domains drastically differs, indicated by a relative rotation and translation of 51.4°and 28.0 Å, respectively, between the helical domains of MtaC and MetH. An orientation similar to that in MtaC was found in the structure of the complex between the cobalaminand AdoMet-binding domains of MetH (39).…”
Section: Structure Of Mtab and The Binding Mode Of The Catalytic Zincmentioning
confidence: 82%
“…In contrast, the helical domain and the N-terminal arm, both multiply anchored to the protein, essentially remain at their positions and prevent a dissociation of MtaC from the protein complex during the reaction cycle. Moreover, reorientation of the Rossmann relative to the helical domains is a well known process (39) owing to the flexible linker between them that serve as hinge (Figs. 1 and 4).…”
Section: Structure Of Mtab and The Binding Mode Of The Catalytic Zincmentioning
confidence: 99%
“…7), are surrounded by hydrophobic groups, whereas the A, B, and D ring acetamides are hydrogen bonded to protein backbone or side chains. The ␣͞␤ domain that binds cobalamin was added by superimposing the known structures of cobalamin-binding domains from MetH (7,18) onto the modeled cobalamin complexes. The resulting model structures resemble glutamate mutase and MMCoA mutase, which are also (␤␣) 8 barrels positioned atop a related Rossmann domain that binds cobalamin.…”
Section: Resultsmentioning
confidence: 99%
“…The structure of a fragment of E. coli MetH that spans both the cobalamin-and AdoMet-binding modules revealed that the four-helix Cap domain moves Ϸ25 Å to allow formation of an intramolecular complex that is competent for the reactivation reaction in which AdoMet is the methyl donor to cob(I)alamin (18).…”
mentioning
confidence: 99%
“…The crystal structure of the His759Gly variant of the Cterminal half of MetH (residues 649-1227) was solved recently (11). His-759 supplies the imidazole ligand to cobalt in the wild-type protein, and in its absence methylcobalamin lacks a coordinated imidazole (it is base-off) and exhibits a shift in absorbance maximum from 525 nm (red) to 450 nm (yellow).…”
mentioning
confidence: 99%